Comparative Evaluation of β-Cyclodextrin Inclusion Complexes with Eugenol, Eucalyptol, and Clove Essential Oil: Characterisation and Antimicrobial Activity Assessment for Pharmaceutical Applications - Alina Ionela Stancu; Magdalena Mititelu; Anton Ficai; Lia-Mara Ditu; Mihaela Buleandră; Irinel Adriana Badea; Elena Pincu; Marius Constantin Stoian; Oana Brîncoveanu; Adina Boldeiu; Eliza Oprea (Pharmaceutics)
Clove essential oil (Eugenia caryophyllata essential oil, ECEO) is known for its high eugenol content and notable antimicrobial properties. However, the volatility and instability of its active compounds hinder broader pharmaceutical applications. Methods: This study characterised the chemical composition of ECEO and comparatively evaluated four β-cyclodextrin (β-CD) encapsulation methods: kneading, co-precipitation, lyophilisation, and co-precipitation–lyophilisation for eugenol, eucalyptol, and ECEO. Encapsulation efficiency, physicochemical properties, and antimicrobial potential were assessed. Analytical techniques included Gas Chromatography–Mass Spectrometry (GC-MS), Headspace GC-MS (HS-GC-MS), Differential Scanning Calorimetry (DSC), Job’s method, and Dynamic Light Scattering (DLS). Results: GC-MS identified eugenol (90.67%), eugenyl acetate (4.77%), and (E)–β-caryophyllene (3.98%) as major components of ECEO, while HS-GC-MS indicated a slightly reduced eugenol content (86.46%). The kneading method yielded the highest encapsulation efficiency for eugenol, whereas the co-precipitation–lyophilisation method was optimal for eucalyptol. DSC thermograms confirmed complex formation, and DLS analysis revealed nanostructures averaging 186.4 nm in diameter (PDI = 0.298). Antimicrobial assays showed MIC values ranging from 0.039 mg/mL to 10,000 mg/mL. Notably, ECEO and its β-CD complex displayed enhanced efficacy against Escherichia coli (0.039 mg/mL), surpassing the reference antibiotic gentamicin (0.049 mg/mL). Conclusions: β-Cyclodextrin encapsulation significantly enhances the stability and bioactivity of volatile antimicrobial compounds, thereby supporting their potential integration into advanced essential oil-based pharmaceutical formulations.